A pathogen effector co-opts a host RabGAP protein to remodel pathogen interface and subvert defense-related secretion - Yuen,ELH; Tumtas,Y; King,F; Ibrahim,T; Chan,LI; Evangelisti,E; Tulin,F; Skenar,J; Menke,FLH; Kamoun,S; Bubeck,D; Schornack,S; et al. (Science Advances, 2024)
Pathogens have evolved sophisticated mechanisms to manipulate host cell membrane dynamics, a crucial adaptation to survive in hostile environments shaped by innate immune responses. Plant-derived membrane interfaces, engulfing invasive hyphal projections of fungal and oomycete pathogens, are prominent junctures dictating infection outcomes. Understanding how pathogens transform these host-pathogen interfaces to their advantage remains a key biological question. Here, we identified a conserved effector, secreted by plant pathogenic oomycetes, that co-opts a host Rab GTPase-activating protein (RabGAP), TOPGAP, to remodel the host-pathogen interface. The effector, PiE354, hijacks TOPGAP as a susceptibility factor to usurp its GAP activity on Rab8a, a key Rab GTPase crucial for defense-related secretion. By hijacking TOPGAP, PiE354 purges Rab8a from the plasma membrane, diverting Rab8a-mediated immune trafficking away from the pathogen interface. This mechanism signifies an uncanny evolutionary adaptation of a pathogen effector in co-opting a host regulatory component to subvert defense-related secretion, thereby providing unprecedented mechanistic insights into the reprogramming of host membrane dynamics by pathogens.